Calcium-titanium co-coated modified sodium battery positive electrode material as well as preparation method and application thereof

By forming a perovskite cladding layer on the surface of the sodium electropositive electrode material, the problem of poor circulation stability of the material is solved, the air stability and circulation performance are improved, the Na2CO3 content is significantly reduced, and the safety performance of the battery is enhanced.

CN119181790APending Publication Date: 2024-12-24GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411529812.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The circulation stability of existing sodium electropositive electrode materials is poor, easily reacting with air, causing the formation of moisture and residual alkali, affecting processing performance and circulation ability, and easily destroying the material structure during long cycles, affecting battery safety performance.

Method used

Perovsk co-coated modified sodium electropositive electrode material is used to form a cladding layer of Ca and Ti on the surface of the matrix material, which reduces the residual alkali on the surface of the material, improves air stability and enhances structural stability, and improves processing and cycling performance.

Benefits of technology

It significantly reduces the Na2CO3 content, improves the air stability and circulation performance of the material, extends the cycle life of the battery, and enhances the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181790A_ABST
    Figure CN119181790A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion battery positive electrode materials, in particular to a calcium-titanium co-coated modified sodium-ion battery positive electrode material as well as a preparation method and application thereof. Wherein the calcium-titanium co-coated modified sodium battery positive electrode material comprises a base material and a coating material coated on the surface of the base material, the composition of the base material is NaxNiaFebMncMdO2, M is at least one of Zn, Ca, Li, Mg, K, Ti, Al, Cu, B, Sn, Sb and Bi, and the coating material comprises a Ca source and a Ti source. The coating layer is formed on the surface of the positive electrode material through a Ca and Ti co-coating method, Ti can reduce residual alkali on the surface of the material and form a stable structure Na2Ti3O7, and Ca can form an inert coating layer on the surface of the positive electrode material, so that the residual alkali on the surface of the material is reduced, the air stability of the material is improved, the contact between the material and an electrolyte is reduced, and the service life of the material is prolonged. Further, the processing performance and the cycle performance of the positive electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a calcium-titanium co-coated modified sodium battery positive electrode material, and a preparation method and application thereof. Background Art

[0002] Due to the advantages of low price and wide distribution of sodium resources, the research on sodium-ion batteries and their key electrode materials has attracted widespread attention in recent years. Compared with lithium batteries, the biggest change in sodium-ion batteries is the positive electrode material, which is also a key factor in determining the battery's energy density, safety, cycle life and other performance. There are three main types of positive electrode materials for sodium-ion batteries: layered oxides, Prussian blue compounds, and polyanion compounds. Among them, layered oxide positive electrode materials have higher specific capacity and more mature technical routes, similar production processes to lithium batteries, and equipment that can be used with lithium batteries, which can achieve large-scale mass production faster. However, due to its unique crystal structure, layered oxides have the following shortcomings: 1) It is easy to react with air during processing and storage, resulting in higher moisture, pH and residual alkali, etc., affecting subsequent processing performance and cycle capacity; 2) The production process of positive electrode materials is prone to generate a large amount of Na2CO3, resulting in excessive gas production during the long cycle of the full battery, affecting the safety performance of the battery; 3) The positive electrode material is in contact with the electrolyte during the long cycle, which is prone to damage to the material structure, resulting in poor cycle performance. Therefore, it is necessary to find suitable methods to reduce its residual alkali and improve its air stability and material structure stability in order to improve its processing performance and long-cycle stability, expand the application scope of sodium battery positive electrode materials and improve their commercial value. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor cycle stability of existing sodium battery positive electrode materials, thereby providing a calcium-titanium co-coated modified sodium battery positive electrode material and its preparation method and application to solve the above problem.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] A calcium-titanium co-coated modified sodium positive electrode material, the calcium-titanium co-coated modified sodium positive electrode material comprising a base material and a coating material coated on the surface of the base material, wherein the base material is composed of Na x Ni a Fe b Mn c M dO2, 0.9≤x≤1.05, 0.2≤a≤0.5, 0.2≤b≤0.5, 0.2≤c≤0.5, 0.01≤d≤0.1, a+b+c+d=1, M is at least one of Zn, Ca, Li, Mg, K, Ti, Al, Cu, B, Sn, Sb, Bi, and the coating material includes a Ca source and a Ti source.

[0006] Preferably, the molar ratio of Ca to Ti in the coating material is (1-30):1, preferably 1:1.

[0007] Preferably, the mass ratio of the base material to the coating material is 100:(0.5-3).

[0008] Preferably, the Ca source comprises calcium carbonate;

[0009] And / or, the Ti source includes TiO2.

[0010] The present invention also provides a method for preparing the above-mentioned calcium-titanium co-coated modified sodium positive electrode material, comprising: weighing a sodium source, a nickel source, an iron source, a manganese source and an M source according to the stoichiometric ratio of the matrix material and calcining the calcined material to obtain a burnt material; sintering the burnt material with a Ca source and a Ti source to obtain the calcium-titanium co-coated modified sodium positive electrode material.

[0011] Preferably, the sodium source comprises Na2CO3;

[0012] And / or, the nickel source comprises NiO;

[0013] and / or, the iron source comprises Fe2O3;

[0014] and / or, the manganese source comprises MnO2;

[0015] And / or, the M source includes at least one of ZnO, CaO, Li2O, MgO, K2O, TiO2, Al2O3, CuO, B2O3, SnO2, Sb2O3, and Bi2O3.

[0016] Preferably, the temperature program of the calcination treatment is: firstly heating to 500-850°C and keeping it for 3-6 hours, and then heating to 800-1200°C and keeping it for 5-15 hours.

[0017] Preferably, the atmosphere of the calcination treatment is air and / or oxygen;

[0018] And / or, the heating rate of the calcination treatment is 1-5°C / min;

[0019] And / or, the calcination treatment is followed by natural cooling and pulverization and sieving.

[0020] Preferably, the sintering temperature is 600-900°C;

[0021] And / or, the sintering treatment time is 3-8h;

[0022] And / or, the heating rate of the sintering treatment is 1-5°C / min;

[0023] And / or, the sintering atmosphere is air and / or oxygen;

[0024] And / or, after the sintering treatment, the sintered product is further cooled naturally and crushed and sieved to remove iron.

[0025] The present invention also provides the use of the above-mentioned calcium-titanium co-coated modified sodium electric positive electrode material or the calcium-titanium co-coated modified sodium electric positive electrode material prepared by the above-mentioned preparation method of the calcium-titanium co-coated modified sodium electric positive electrode material in sodium ion batteries.

[0026] The technical solution of the present invention has the following advantages:

[0027] A calcium-titanium co-coated modified sodium positive electrode material, the calcium-titanium co-coated modified sodium positive electrode material comprising a base material and a coating material coated on the surface of the base material, wherein the base material is composed of Na x Ni a Fe b Mn c M d O2, 0.9≤x≤1.05, 0.2≤a≤0.5, 0.2≤b≤0.5, 0.2≤c≤0.5, 0.01≤d≤0.1, a+b+c+d=1, M is at least one of Zn, Ca, Li, Mg, K, Ti, Al, Cu, B, Sn, Sb, Bi, and the coating material includes a Ca source and a Ti source. The present invention forms a coating layer on the surface of the positive electrode material by a Ca and Ti co-coating method, wherein Ti reduces the residual alkali on the surface of the material to form a stable structure Na2Ti3O7, and Ca forms an inert coating layer on the surface of the positive electrode material, thereby reducing the residual alkali on the surface of the material, improving the air stability of the material, reducing the contact between the material and the electrolyte, and thus improving the processing performance and cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1This is a SEM morphology of the calcium-titanium co-coated modified sodium battery positive electrode material prepared in Example 1 of the present invention;

[0030] Figure 2 This is the XRD diagram of the calcium-titanium co-coated modified sodium battery positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0032] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0033] Example 1

[0034] This embodiment provides a method for preparing a sodium-based positive electrode material co-coated with calcium and titanium, and the specific steps are as follows:

[0035] 1) According to NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 Na2CO3, NiO, Fe2O3, MnO2 and CaO were weighed and mixed evenly in a box furnace and calcined at 850℃ for 4h in air atmosphere, and then calcined at 1000℃ for 10h with a heating rate of 2℃ / min. After cooling naturally, NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 O2-burning material;

[0036] 2) Weigh NaNi in a mass ratio of 100:1 0.33 Fe 0.33 Mn 0.33 Ca 0.01 After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 with a mass ratio of 1:1) are mixed evenly, they are placed in a box furnace and sintered at 700℃ in an air atmosphere for 6 hours at a heating rate of 2℃ / min. After natural cooling, the calcium-titanium co-coated modified sodium positive electrode material is obtained after crushing, passing through a 250-mesh sieve and removing iron. Its SEM morphology is shown in the figure. Figure 1 The XRD test results are shown in Figure 2As shown, according to Figure 1 and Figure 2 It can be seen that the calcium-titanium co-coated modified sodium battery positive electrode material prepared in this embodiment has a single crystal morphology and is an O3 phase (XRD standard card PDF#88-5720).

[0037] Example 2

[0038] This embodiment provides a method for preparing a sodium-based positive electrode material co-coated with calcium and titanium, and the specific steps are as follows:

[0039] 1) According to Na 1.05 Ni 0.32 Fe 0.32 Mn 0.32 Ti 0.04 The stoichiometric ratio of Na2CO3, NiO, Fe2O3, MnO2 and TiO2 was weighed and mixed evenly, placed in a box furnace and calcined at 700℃ in air atmosphere for 5h, then calcined at 1050℃ for 10h, with a heating rate of 5℃ / min. After natural cooling, Na2CO3 was crushed and passed through a 250-mesh sieve to obtain 1.05 Ni 0.32 Fe 0.32 Mn 0.32 Ti 0.04 O2-burning material;

[0040] 2) Weigh Na in a mass ratio of 100:2 1.05 Ni 0.32 Fe 0.32 Mn 0.32 Ti 0.04 After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 in a mass ratio of 1:1) are evenly mixed, they are placed in a box furnace and sintered at 800°C in an air atmosphere for 6 hours at a heating rate of 5°C / min. After natural cooling, they are crushed, sieved through a 250-mesh sieve and iron is removed to obtain a calcium-titanium co-coated modified sodium battery positive electrode material.

[0041] Example 3

[0042] This embodiment provides a method for preparing a sodium-based positive electrode material co-coated with calcium and titanium, and the specific steps are as follows:

[0043] 1) According to Na 0.96 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Ti 0.05The stoichiometric ratio of Na2CO3, NiO, Fe2O3, MnO2, ZnO and TiO2 was weighed and mixed evenly, placed in a box furnace and calcined at 600℃ in air atmosphere for 6h, then calcined at 950℃ for 15h, with a heating rate of 1℃ / min. After natural cooling, Na2CO3 was crushed and passed through a 250-mesh sieve to obtain 0.96 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Ti 0.05 O2-burning material;

[0044] 2) Weigh Na in a mass ratio of 100:1.55 0.96 Ni 0.3 Fe 0.3 Mn 0.3 Zn 0.05 Ti 0.05 After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 with a mass ratio of 30:1) are mixed evenly, they are placed in a box furnace and sintered at 900°C in an air atmosphere for 4 hours with a heating rate of 1°C / min. After natural cooling, they are crushed, sieved through a 250-mesh sieve and iron removed to obtain the calcium-titanium co-coated modified sodium battery positive electrode material.

[0045] Example 4

[0046] This embodiment provides a method for preparing a sodium-based positive electrode material co-coated with calcium and titanium, and the specific steps are as follows:

[0047] 1) According to Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Li 0.02 K 0.03 Mg 0.05 Na2CO3, NiO, Fe2O3, MnO2, Li2O, K2O, and MgO were weighed and mixed evenly, placed in a box furnace and calcined at 850℃ for 3h in air atmosphere, and then calcined at 1200℃ for 5h with a heating rate of 2℃ / min. After natural cooling, Na2CO3 was crushed and passed through a 250-mesh sieve to obtain Na 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Li 0.02 K 0.03 Mg 0.05 O2-burning material;

[0048] 2) Weigh Na in a mass ratio of 100:0.5 0.9 Ni 0.3 Fe0.3 Mn 0.3 Li 0.02 K 0.03 Mg 0.05 After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 in a mass ratio of 1:1) are evenly mixed, they are placed in a box furnace and sintered at 600°C in an air atmosphere for 8 hours with a heating rate of 2°C / min. After natural cooling, they are crushed, sieved through a 250-mesh sieve and iron removed to obtain a calcium-titanium co-coated modified sodium battery positive electrode material.

[0049] Example 5

[0050] This embodiment provides a method for preparing a sodium-based positive electrode material co-coated with calcium and titanium, and the specific steps are as follows:

[0051] 1) According to NaNi 0.3 Fe 0.3 Mn 0.3 Cu 0.02 B 0.03 Al 0.05 Na2CO3, NiO, Fe2O3, MnO2, CuO, B2O3, Al2O3 were weighed and mixed evenly, placed in a box furnace and calcined at 500℃ in air atmosphere for 6h, then calcined at 800℃ for 15h, with a heating rate of 2℃ / min. After natural cooling, NaNi 0.3 Fe 0.3 Mn 0.3 Cu 0.02 B 0.03 Al 0.05 O2-burning material;

[0052] 2) Weigh NaNi in a mass ratio of 100:3 0.3 Fe 0.3 Mn 0.3 Cu 0.02 B 0.03 Al 0.05 After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 in a mass ratio of 1:1) are mixed evenly, they are placed in a box furnace and sintered at 900°C in an air atmosphere for 3 hours at a heating rate of 2°C / min. After natural cooling, they are crushed, sieved through a 250-mesh sieve and iron is removed to obtain a calcium-titanium co-coated modified sodium battery positive electrode material.

[0053] Example 6

[0054] This embodiment provides a method for preparing a sodium-based positive electrode material co-coated with calcium and titanium, and the specific steps are as follows:

[0055] 1) According to Na 0.9 Ni0.3 Fe 0.3 Mn 0.3 Sn 0.02 Sb 0.03 Bi 0.05 Na2CO3, NiO, Fe2O3, MnO2, SnO2, Sb2O3, Bi2O3 were weighed and mixed evenly, placed in a box furnace and calcined at 850℃ for 4h in air atmosphere, then calcined at 1000℃ for 10h with a heating rate of 2℃ / min. After cooling naturally, Na2CO3 was crushed and passed through a 250-mesh sieve to obtain Na 0. 9Ni 0.3 Fe 0.3 Mn 0.3 Li 0.02 K 0.03 Mg 0.05 O2-burning material;

[0056] 2) Weigh Na in a mass ratio of 100:1 0.9 Ni 0.3 Fe 0.3 Mn 0.3 Li 0.02 K 0.03 Mg 0.05 After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 in a mass ratio of 1:1) are mixed evenly, they are placed in a box furnace and sintered at 700°C in an air atmosphere for 6 hours with a heating rate of 2°C / min. After natural cooling, they are crushed, sieved through a 250-mesh sieve and iron is removed to obtain a calcium-titanium co-coated modified sodium battery positive electrode material.

[0057] Comparative Example 1

[0058] This comparative example provides a method for preparing a sodium positive electrode material, and the specific steps are as follows:

[0059] According to NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 Na2CO3, NiO, Fe2O3, MnO2 and CaO were weighed and mixed evenly in a box furnace and calcined at 850℃ for 4h in air atmosphere, and then calcined at 1000℃ for 10h with a heating rate of 2℃ / min. After cooling naturally, NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 O2 obtains sodium positive electrode material.

[0060] Comparative Example 2

[0061] This comparative example provides a method for preparing a sodium positive electrode material, and the specific steps are as follows:

[0062] 1) According to NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Na2CO3, NiO, Fe2O3 and MnO2 were weighed and mixed evenly in a box furnace and calcined at 850℃ for 4h in air atmosphere, and then calcined at 1000℃ for 10h at a heating rate of 2℃ / min. After natural cooling, NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2-burning material;

[0063] 2) Weigh NaNi in a mass ratio of 100:1 1 / 3 Fe 1 / 3 Mn 1 / 3 After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 in a mass ratio of 1:1) are mixed evenly, they are placed in a box furnace and sintered at 700°C in an air atmosphere for 6 hours at a heating rate of 2°C / min. After natural cooling, the sodium positive electrode material is obtained by crushing, passing through a 250-mesh sieve and removing iron.

[0064] Comparative Example 3

[0065] This comparative example provides a method for preparing a sodium positive electrode material, and the specific steps are as follows:

[0066] 1) According to Na 1.1 Ni 0.33 Fe 0.33 Mn 0.33 Ca 0.01 Na2CO3, NiO, Fe2O3, MnO2 and CaO were weighed and mixed evenly in a box furnace and calcined at 850℃ for 4h in air atmosphere, and then calcined at 1000℃ for 10h at a heating rate of 2℃ / min. After natural cooling, Na2CO3 was crushed and passed through a 250-mesh sieve to obtain Na 1.1 Ni 0.33 Fe 0.33 Mn 0.33 Ca 0.01 O2-burning material;

[0067] 2) Weigh Na in a mass ratio of 100:1 1.1 Ni 0.33 Fe 0.33 Mn 0.33 Ca 0.01After the O2-sintered material and the coating material (a mixture of CaCO3 and TiO2 in a mass ratio of 1:1) are mixed evenly, they are placed in a box furnace and sintered at 700°C in an air atmosphere for 6 hours at a heating rate of 2°C / min. After natural cooling, the sodium positive electrode material is obtained by crushing, passing through a 250-mesh sieve and removing iron.

[0068] Comparative Example 4

[0069] This comparative example provides a method for preparing a sodium positive electrode material, and the specific steps are as follows:

[0070] 1) According to NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 Na2CO3, NiO, Fe2O3, MnO2 and CaO were weighed and mixed evenly in a box furnace and calcined at 850℃ for 4h in air atmosphere, and then calcined at 1000℃ for 10h with a heating rate of 2℃ / min. After cooling naturally, NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 O2-burning material;

[0071] 2) Weigh NaNi in a mass ratio of 100:1 0.33 Fe 0.33 Mn 0.33 Ca 0.01 After the O2-sintered material is evenly mixed with CaCO3, it is placed in a box furnace and sintered at 700°C in an air atmosphere for 6 hours with a heating rate of 2°C / min. After natural cooling, it is crushed, sieved through a 250-mesh sieve and iron is removed to obtain the sodium positive electrode material.

[0072] Comparative Example 5

[0073] This comparative example provides a method for preparing a sodium positive electrode material, and the specific steps are as follows:

[0074] 1) According to NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 Na2CO3, NiO, Fe2O3, MnO2 and CaO were weighed and mixed evenly in a box furnace and calcined at 850℃ for 4h in air atmosphere, and then calcined at 1000℃ for 10h with a heating rate of 2℃ / min. After cooling naturally, NaNi 0.33 Fe 0.33 Mn 0.33 Ca0.01 O2-burning material;

[0075] 2) Weigh NaNi in a mass ratio of 100:1 0.33 Fe 0.33 Mn 0.33 Ca 0.01 After the O2-sintered material is evenly mixed with TiO2, it is placed in a box furnace and sintered at 700°C in an air atmosphere for 6 hours with a heating rate of 2°C / min. After natural cooling, it is crushed, sieved through a 250-mesh sieve and iron is removed to obtain the sodium positive electrode material.

[0076] Comparative Example 6

[0077] This comparative example provides a method for preparing a sodium positive electrode material, and the specific steps are as follows:

[0078] 1) According to NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 Na2CO3, NiO, Fe2O3, MnO2 and CaO were weighed and mixed evenly in a box furnace and calcined at 850℃ for 4h in air atmosphere, and then calcined at 1000℃ for 10h with a heating rate of 2℃ / min. After cooling naturally, NaNi 0.33 Fe 0.33 Mn 0.33 Ca 0.01 O2-burning material;

[0079] 2) Weigh NaNi in a mass ratio of 100:1 0.33 Fe 0.33 Mn 0.33 Ca 0.01 After the O2-sintered material is evenly mixed with ZrO2, it is placed in a box furnace and sintered at 700°C in an air atmosphere for 6 hours with a heating rate of 2°C / min. After natural cooling, it is crushed, sieved through a 250-mesh sieve and iron is removed to obtain the sodium positive electrode material.

[0080] Test Example 1

[0081] The positive electrode materials prepared in the above examples and comparative examples were used as positive electrode active materials and slurried with polyvinylidene fluoride and carbon black in a mass ratio of 95:2.5:2.5. The compacted density of the electrode sheet was 3.2 g / cm 3, made into pole pieces, using metal lithium sheets as counter electrodes, glass fiber as separators, and ethylene carbonate (EC) and dimethyl carbonate (DMC) solutions containing 1 mol / L lithium hexafluorophosphate (the volume ratio of EC to DMC being 1:1) as electrolytes, assembled into CR2032 button cells in an argon-filled glove box, and finally placed the batteries in a blue-electric test system for electrical performance testing.

[0082] Among them, the charge / discharge specific capacity test method is: at room temperature, charge to 4.0V at a constant current of 0.1C charge rate, and then discharge to 2.0V at a discharge rate of 0.1C. The charge specific capacity test results are shown in Table 1; the cycle test method is: 50 cycles of charge and discharge test at a rate of 1C / 1C between 2.0-4.0V to characterize the capacity retention rate of the positive electrode material after 50 cycles. The cycle retention rate test results are shown in Table 1; the Na2CO3 content test method is: weigh 10g of sample and dissolve it in 100mL of ultrapure water, take the supernatant after centrifugation, add cresol red-methylene blue mixed indicator, titrate with 0.1M hydrochloric acid, and calculate it from the hydrochloric acid consumption. The initial Na2CO3 content of the sample and the Na2CO3 content exposed to air for 1 day and 3 days were tested respectively. The Na2CO3 content test results are shown in Table 2.

[0083] Table 1

[0084]

[0085]

[0086] Table 2

[0087]

[0088]

[0089] It can be seen from the data in Table 1 and Table 2 that the uncoated positive electrode material in Comparative Example 1 shows a higher Na2CO3 content, and after being placed in the air for 1 day and 3 days, the Na2CO3 content rises sharply, and the buckle cycle also performs poorly, which is not conducive to the safety performance and long cycle stability of the battery. In Comparative Examples 4-6, after coating, the Na2CO3 content of the material decreases to a certain extent, and the cycle performance is improved to a certain extent. After co-coating with Ca and Ti, the Na2CO3 content of the positive electrode material prepared in Examples 1-6 is significantly reduced, and after being placed for 1 day and 3 days, respectively, the Na2CO3 content still grows slowly, showing excellent air stability, 0.1C charging capacity and cycle performance. In addition, it can be seen from Examples 1-6 and Comparative Examples 2-3 that suitable doping and Na content will also affect the Na2CO3 content, capacity and cycle performance.

[0090] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A calcium-titanium co-coated modified sodium positive electrode material, characterized in that: The calcium-titanium co-coated modified sodium positive electrode material comprises a base material and a coating material coated on the surface of the base material, wherein the base material is composed of Na x Ni a Fe b Mn c M d O2, 0.9≤x≤1.05, 0.2≤a≤0.5, 0.2≤b≤0.5, 0.2≤c≤0.5, 0.01≤d≤0.1, a+b+c+d=1, M is at least one of Zn, Ca, Li, Mg, K, Ti, Al, Cu, B, Sn, Sb, Bi, and the coating material includes a Ca source and a Ti source.

2. The calcium-titanium co-coated modified sodium positive electrode material according to claim 1, characterized in that: The molar ratio of Ca to Ti in the coating material is (1-30):1, preferably 1:

1.

3. The calcium-titanium co-coated modified sodium positive electrode material according to claim 1 or 2, characterized in that: The mass ratio of the base material to the coating material is 100:(0.5-3).

4. The calcium-titanium co-coated modified sodium positive electrode material according to any one of claims 1 to 3, characterized in that: The Ca source includes calcium carbonate; And / or, the Ti source includes TiO2.

5. A method for preparing the calcium-titanium co-coated modified sodium positive electrode material according to any one of claims 1 to 4, characterized in that: include: According to the stoichiometric ratio of the base material, sodium source, nickel source, iron source, manganese source and M source are weighed and calcined to obtain a sintered material; the sintered material is sintered with the Ca source and the Ti source to obtain the perovskite co-coated modified sodium positive electrode material.

6. The preparation method according to claim 5, characterized in that: The sodium source includes Na2CO3; And / or, the nickel source comprises NiO; and / or, the iron source comprises Fe2O3; and / or, the manganese source comprises MnO2; And / or, the M source includes at least one of ZnO, CaO, Li2O, MgO, K2O, TiO2, Al2O3, CuO, B2O3, SnO2, Sb2O3, and Bi2O3.

7. The preparation method according to claim 5 or 6, characterized in that: The temperature program of the calcination treatment is: firstly heating to 500-850°C and keeping it for 3-6 hours, and then heating to 800-1200°C and keeping it for 5-15 hours.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The calcination atmosphere is air and / or oxygen; And / or, the heating rate of the calcination treatment is 1-5°C / min; And / or, the calcination treatment is followed by natural cooling and pulverization and sieving.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The sintering temperature is 600-900°C; And / or, the sintering treatment time is 3-8h; And / or, the heating rate of the sintering treatment is 1-5°C / min; And / or, the sintering atmosphere is air and / or oxygen; And / or, after the sintering treatment, the sintered product is further cooled naturally and crushed and sieved to remove iron.

10. Use of the calcium-titanium co-coated modified sodium battery positive electrode material described in claims 1-4 or the calcium-titanium co-coated modified sodium battery positive electrode material prepared by the preparation method of the calcium-titanium co-coated modified sodium battery positive electrode material described in claims 5-9 in sodium ion batteries.